Analisis Kualitas Kompos Limbah Upacara Agama Hindu di Denpasar dengan EM4 sebagai Dekomposer - WERAYOGA, I MADE; ATMAJA, I WAYAN DANA; SUWASTIKA, A A NGURAH GEDE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Analysis of the Compost Quality of Hindu Ceremony Wastein Denpasar with EM4 as a Dekomposer The aim of this research was to find out best quality of compost made of by the waste of Hindu ceremony in Denpasar, cow dung, and bran, with EM4 as a decomposer. The research was conducted on November 2014 until June 2015, located at pegok experimental field, faculty of agriculture, Udayana university. The design used was Randomized block design with two factors, the first factor was combination the waste of Hindu ceremony and the second factor was the decomposer consisted of without decomposer and with EM4 with dose of 200 mL (dilution 20 mL EM4 + 10 g sugar + 1 liter water). Compost quality was known by counting the total bacterial population, total fungi population, and respiration, measuring the temperature, water content, weight, structure, smell, color, measuring the content of total N, total P, total K, C-organic, the C/N ratio, and the pH. The result of research based on statistical analysis show that interaction impact between combination the Waste of Hindu ceremony and decomposer only have real influence on the parameter of total bacterial population, total fungi population, N-total, and P-total of compos. The research resulting in several conclusions that is the treatment of 75% the waste of Hindu ceremony + 15% cow dung +10%bran presenting the best quality of compost showed by the height of total bacterial population ( 17,38 x 108 cpu g-1 of compost), highest N-total (1,82%), the lowest content of C-organic (10,39%), highest P-total (83,71 mg/100g).
Keywords: EM4; the waste of Hindu ceremony; compost quality